Psychosocial Impact of COVID-19 on Healthcare Workers at a Tertiary Care Cardiac Center of Karachi Pakistan. Issue 2 (February 2021) - Kumar, Dileep; Saghir, Tahir; Ali, Gulzar; Yasin, Umamah; Furnaz, Shumaila; Karim, Musa; Hussain, Muhammad; Kumari, Rekha; Bai, Reeta; Kumar, Hitesh
Abstract : Objectives: Aim of this study was to determine the depression, stress, and anxiety level among healthcare workers working at a tertiary care cardiac center of Karachi Pakistan during COVID-19 pandemic. Methods: This survey was conducted at the National Institute of Cardiovascular Disease (NICVD), Karachi, Pakistan. Participants of the study were fulltime employees of hospital. Data were collected using an online questionnaire and Depression, Anxiety and Stress - 21 (DASS-21) scale was used. Results: A total of 224 healthcare workers were included, 46 (20.5%) participants were screened for moderate to severe depression, 20.1% (45) for moderate to severe anxiety, and 14.7% (33) for moderate to severe stress. Conclusion: A significant levels of depression, anxiety, and stress were noted with the major concerns of workplace exposure, increased risk of infection, and transmission to their families and friends.